Anatomical variations of cystic artery: A digital subtraction angiography study - Çelebioğlu, Emre Can; Akkaşoğlu, Sinem (Journal of Surgery and Medicine, 2021)
Background/Aim: Branching variations in the cystic and hepatic arteries may lead to bleeding and mortal complications during surgery. This study aimed to demonstrate the relationship between cystic artery (CA) variations and hepatic artery branching patterns among an Anatolian population using Michel’s classification and compare the distribution of these variations among genders. Methods: Angiographies performed between 2014-2017 were retrospectively evaluated and DSA images of 303 patients (84 females and 219 males) were included in this cross-sectional study. Michel’s classifications of the hepatic arteries and CA variations of the patients were noted, and each was analyzed separately, along with gender-related branching differences. Results: Hepatic arteries of 256 patients could be evaluated according to Michel’s classification, the most frequent being Michel’s class I (69.9 %). Thirty patients (9.9%) were excluded from CA-related statistical analyses since they had undergone a cholecystectomy. CAs were not visualized in fifty-five (18.2%) of the remaining patients. Of the 218 patients with apparent CAs, eleven females (19.3%) and twenty males (12.4%) had double cystic arteries (P=0.201). Two hundred and twelve (85.1%) CAs originated from the right hepatic artery (RHA), which was the most common parent artery. No significant relationship was found between Michel’s classification and CA origin among different genders (P=0.532). Conclusion: An overlooked anatomic variation could lead to many iatrogenic complications during diagnostic and therapeutic interventions; thus, variations of the vascular structures have attracted medical professionals’ interest. This study focuses on the variations of the cystic artery and its relationship with hepatic arterial branching variations.